2021
DOI: 10.1021/acsomega.1c02295
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive and Flexible Metal–Organic Framework Polymer-Based H2S Gas Sensor

Abstract: We report the fabrication of a novel metal−organic framework (MOF)−polymer mixed-matrix flexible membrane for the detection of hydrogen sulfide (H 2 S) gas at room temperature. This high-performance gas sensor is based on MOF-5 microparticles embedded on a conductivity-controlled chitosan (CS) organic membrane. The conductivity of the organic membrane is controlled by blending it with a glycerol ionic liquid (IL) at different concentrations. The sensor showed a remarkable detection sensitivity for H 2 S gas at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…It is, therefore, the synergistic effect of the highly connected molecules of the proposed nanocomposite membrane that explains its high efficiency and sensitivity toward H 2 S gas. The high porosity of the MOF component of the composite membrane was previously proven to contribute to the passage of H 2 S molecules within the composite membrane [ 38 ]. The current findings support the contribution of the highly porous MOF structures in the construction of a gas sensor assembly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is, therefore, the synergistic effect of the highly connected molecules of the proposed nanocomposite membrane that explains its high efficiency and sensitivity toward H 2 S gas. The high porosity of the MOF component of the composite membrane was previously proven to contribute to the passage of H 2 S molecules within the composite membrane [ 38 ]. The current findings support the contribution of the highly porous MOF structures in the construction of a gas sensor assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ILs are suitable to be used for the fabrication of electrochemical sensors as they are environmentally friendly [ 32 , 33 ]. It has been shown that glycerol-IL can be used effectively to control the conductivity of PVA membranes [ 37 , 38 ], thus, it will be utilized in this work. A volume of 5 vol% of IL (glycerol) was mixed in a 20 mL of the PVA stock solution, which was also doped with Cu-MOF that was suspended in 2.5 mL of DW at 70 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By taking advantage of the cage-bridge structure of MOF-5 ([Zn 4 O(BDC) 3 ] n ), Ali et al [95] developed a high-performance gas sensor for the low concentration detection of H 2 S gas molecules (1 ppm) at room temperature. The sensing components of the device consisted of MOF-5 microparticles, blended and embedded in a conductivity-controlled chitosan organic membrane resulting in the fabrication of a flexible gas sensor (Figure 5f, inset).…”
Section: Hydrogen Sulphide (H 2 S)mentioning
confidence: 99%
“…Organic polymers, such as PVA, are characterized by their wide abundance and their known promising properties, such as flexibility, environmental friendliness, thermal stability and the ability to form electrolytes by virtue of their hydrophilic nature [35]. Moreover, the conductivity of PVA can be controlled by doping it with an ionic liquid (IL), such as glycerol [36][37][38]. These combined properties can be further exploited by doping the polymer matrix with materials that have an affinity toward the detection of H 2 S gas, so that changes in their conductivity or resistivity can be recorded.…”
Section: Introductionmentioning
confidence: 99%